Ginsenoside Rg1 improved diabetes through regulating the intestinal microbiota in high‐fat diet and streptozotocin‐induced type 2 diabetes rats. Issue 10 (19th July 2022) - Peng, Man; Wang, Liming; Su, Hui; Zhang, Lei; Yang, Yue; Sun, Le; Wu, Yi; Ran, Lei; Liu, Sida; Yin, Min; Li, Shude; Chunyu, Weixun
Abstract: Ginsenoside Rg1 is the active ingredient of the plant named genus Panax (ginseng), which exhibited significant bioactivities, including anti‐inflammatory, antioxidation, and anti‐diabetic effects. Herein, 4‐week treatment of ginsenoside Rg1 remarkably decreased blood glucose levels and improved the resistance of insulin, oxidative stress, and inflammation along with lipid profile in T2D rats triggered via high‐fat diet and streptozotocin (STZ). Ginsenoside Rg1 supplementation improved the intestinal microbial composition induced by type 2 diabetes (T2D), which increased the proportions of Lachnospiraceae_NK4A136_group and Lachnoclostridium and decreased the proportions of Lactobacillus . Additionally, Spearman's correlation test between the gut microflora and biomedical assays (| r | > .5) revealed that the Lachnospiraceae_NK4A136_group, Roseburia, and Romboutsia greatly affect intestinal microbiota, which may play pivotal roles in preventing T2D. Our findings illustrate the use of ginsenoside Rg1 as a dietary supplement along with prospective prebiotics due to its ability to alter the gut microflora and alleviate T2D‐linked biochemical abnormalities. Practical applications: This was the first study to elucidate the influences of ginsenosides Rg1 in improving the intestinal microbiota of T2D in SD rats. The data illustrated that the ginsenosides Rg1 remarkably increased the proportions of SCFAs producing bacteria. Hence, ginsenoside Rg1 could be used as a potential prebiotic in the treatment of T2D through alteration of intestinal microbiota. Abstract : Administration of ginsenoside Rg1 can ameliorate high‐fat diet and streptozotocin induced type 2 diabetes (T2D) by mediating the expression of inflammatory cytokines and oxidation stress. The 16S rDNA sequencing showed the ginsenosides Rg1 remarkably increased the proportions of SCFAs producing bacteria. The use of ginsenoside Rg1 as a dietary supplement, which can alter the gut microflora and alleviate T2Dlinked biochemical abnormalities.